Local scour and flow characteristics around pipeline subjected to vortex-induced vibrations - Guan, Dawei (2022)
Although local scour around submarine pipelines has been extensively studied in the last few decades, understanding of the mechanism of local scour around pipelines is still in its infancy stage due to the complex nature of flow-pipeline-seabed interactions, especially when the pipeline is subjected to vibrations. This experimental study aims to obtain an improved perception of the scour mechanism around a pipeline subjected to vortex-induced vibrations. The experiments were conducted in a flow recirculation flume in clear-water scour conditions in which a circular cylinder with diameter (D) of 35 mm was used as the pipeline model. The initial gap (G0) between the underside of the pipeline and undisturbed flat-bed level was 0.45D. The time evolution of the pipeline motion and scour profile around the pipeline was measured using a high-speed camera and laser sources. The flow fields around the vibrating pipeline were obtained using the particle image velocimetry (PIV) technique and phase-average analysis. Based on the characteristics of the development of the scour hole and pipeline motions, three scour stages are identified. The downward motion of the vibrating pipeline and interactions between the counterclockwise vortex (downstream of the pipeline) that sheds from the lower shear layer of the pipeline and sediment bed are found to be the primary mechanisms that cause the formation of the scour holes beneath the pipeline. The interactive coupling effects among the vibrating pipeline, flow field, and scour process also are discussed in this study.